Quality of Services in the Comprehensive Rehabilitation Centers for Individuals with ID: A Descriptive Study using SERVQUAL Model - Abdullah, M. Almanie (Journal of Intellectual Disability - Diagnosis and Treatment, 2022)
This study aimed to investigate the quality of services in the comprehensive rehabilitation centers for individuals with ID using the SERVQUAL model. 128 parents of people with disabilities who benefited from comprehensive rehabilitation centers. An online questionnaire was used to collect data from the target parents. For this study, quantitative survey research was employed. The independent variable is the quality of services, while the dependent variable is the SERVQUAL model. According to the evaluation of parents, results indicated a gap between what was perceived and what was expected quality of services in the comprehensive rehabilitation centers (in all dimensions) in light of the SERVQUAL model for persons with intellectual disabilities. It is concluded that the SERVQUAL model was a good model to investigate the quality of services in the comprehensive rehabilitation centers for individuals with ID.